Miniature mechanical testing of LMD-fabricated compositionally & microstructurally graded γ titanium aluminides - Galgon, Florian; Melzer, Daniel; Zenk, Christopher; Dzugan, Jan; Körner, Carolin (Journal of Materials Research, 2022)
The design freedom in Laser Metal Deposition provided by the absence of a powder bed enables the fabrication of Functionally Graded Materials through Additive Manufacturing. For the first time, two suitable γ-TiAl alloys (TiAl48Cr2Nb2, TiAl45Nb4C) are combined in direct and gradual transitions to generate different microstructure morphologies and, consequently, different mechanical properties within a component after an identical heat treatment. The influence of alloy composition, microstructure type, and material transition on the tensile properties and fracture toughness is analyzed through miniature testing. Miniature tensile tests show no orientation dependency in regard to the build direction and the composition/microstructure transition is not found to be a preferred fracture site. The miniature fracture toughness tests reveal that already small composition changes—insufficient to alter the microstructure configuration—can have a significant effect on the cracking behavior. Graphical abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-11-25
Keywords: Directed energy deposition; Fracture toughness; Functionally graded materials; Laser metal deposition; Miniature testing; Tensile testing; Titanium aluminides